Agrarian extractivism in Latin America. Libro editado por Ben McKay, Alberto Alonso-Fradejas, Arturo Ezquerro-Cañete - Cano Castellanos, Ingreet Juliet (El Colegio de México, 2022)
Within the recent and abundant literature on extractivism in Latin America, the bibliographical contributions specifically aimed at reflecting on the empirical grounds, the theoretical contours and the analytical challenges that can be framed in the category of agrarian extractivism are, in a certain sense, less numerous. The compilation edited by McKay, Alonso-Fradejas and Ezquerro-Cañete shows how the aforementioned literature interpelles researchers with recent work in rural Latin American contexts, who reflect and speak in various ways about agrarian extractivism on the continent. This review looks at the contents of this work considering the discussions that authors have when participating in the collective reflection, but also explores some of the questions that remain open for more and new research.